Socially Extended Scientific Knowledge - Pritchard, Duncan (Frontiers in Psychology, 2022)
A three-tiered account of social cognition is set out--along with the corresponding variety of social knowledge that results from this social cognition--and applied to the special case of scientific collaboration. The first tier is socially-facilitated cognition, which results in socially-facilitated knowledge. This is a form of cognition which, while genuinely social (in that social factors play an important explanatory role in producing the target cognitive success), falls short of socially extended cognition. The second tier is socially extended cognition, which generates socially extended knowledge. This form of cognition is social in the specific sense of the information-processing of other agents forms part of the socially extended cognitive process at issue. It is argued, however, that the core notion of socially extended cognition is individual in nature, in that the target cognitive success is significantly creditable to the socially extended cognitive agency of the individual. Socially extended cognition, in its core sense, thus generates individual knowledge. Finally, there is distributed cognition, which generates distributed knowledge. This is where the cognitive successes produced by a research team are attributable to a group agent rather than to individuals within the team. Accordingly, where this form of social cognition generates knowledge (distributed knowledge), the knowledge is irreducibly group knowledge. It is argued that by making clear this three-tiered structure of social scientific knowledge a prima facie challenge is posed for defenders of distributed scientific cognition and knowledge to explain why this form of social knowledge is being exhibited and not one of the two weaker (and metaphysically less demanding) forms of social knowledge.